Challenging Assumptions Underlying the Metamorphosis Phase: Ethnographic Analysis of Metamorphosis Within an Unemployment Organization. Issue 1 (1st January 2016) - Gist, Angela N.
Abstract : Organizational communication scholars have grappled with assimilation processes and expanded the theoretical conceptualization of each phase. This article joins in conversation with organizational communication scholars by identifying and problematizing the assumption that reaching metamorphosis is always a positive experience. Through the ethnographic analysis of empirical data collected from an unemployment support organization, the author argues that being an established organizational member is sometimes counter to organizational objectives. While traditional organizations attempt to maintain and grow their membership, some alternative organizational formats aim to minimize membership. This premise challenges the assumption that achieving metamorphosis is always a desirable state of organizational membership. Furthermore, this study reveals how communication changes when it is undesirable for service recipients to reach metamorphosis.